2016
DOI: 10.1080/01596306.2016.1141177
|View full text |Cite
|
Sign up to set email alerts
|

Power relations in the enactment of English language education policy for Chinese schools

Abstract: The scale of English language education in China is astounding, but recent research has shown that the latest national English education policy for Chinese schools has not been implemented successfully due to various reasons. One reason given for the lack of success is the impracticability of the top-down policy itself excluding teachers' involvement and neglecting the contextual constraints. Building on the theoretical framework of multi-levelled actors in language planning and language policy, and drawing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In this process, practitioners who are at the ''bottom'' of the chain may not be fully involved in the policy/standard making process, and in turn they may not be well prepared to carry out the policy/standard in teaching. Li (2017) suggests that it may be beneficial to appropriately ''empower the locals,'' since teachers usually ''have their students' best interests in their hearts'' (p. 724). In fact, nowadays the Chinese government is making progress to seek a more equal distribution of power, aiming to create a more just society.…”
Section: Teachers' Perspective (3): Needs and Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this process, practitioners who are at the ''bottom'' of the chain may not be fully involved in the policy/standard making process, and in turn they may not be well prepared to carry out the policy/standard in teaching. Li (2017) suggests that it may be beneficial to appropriately ''empower the locals,'' since teachers usually ''have their students' best interests in their hearts'' (p. 724). In fact, nowadays the Chinese government is making progress to seek a more equal distribution of power, aiming to create a more just society.…”
Section: Teachers' Perspective (3): Needs and Expectationsmentioning
confidence: 99%
“…Particularly, there is limited knowledge in the field about English teachers' views toward CSELA and their needs in putting this new standard into practice. These are important topics in CSELA research because past studies have demonstrated that practitioners are key stakeholders in education reforms, since their beliefs are closely related to their instructional practices, which then influences the ultimate attainment of the reform (e.g., G. Hu, 2005;Li, 2017). Therefore, revealing practitioners' perceptions and needs using a qualitative design may help enrich the field's knowledge of CSELA's potential impact on English teachers.…”
Section: Recent Research On China's Standards Of English Language Abi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such success is attributed to the effective macro-to-micro policy transmission mechanism, featuring clear articulation of the policy to teachers, the professional support teachers receive, and effective teacher-student collaboration. In contrast, Li [21] considered the enactment of China's EFL (English as a foreign language) policy in secondary schools an ineffective case of policy implementation. Evidence gathered from various stakeholders indicated the top-down policymaking strategy failed to consider teachers' voices and the local education realities.…”
Section: Micro Lp In Schoolsmentioning
confidence: 99%
“…With China's growing status and role in the world, the degree of attention to the English education in China gradually rises. The scale of the current English education in China is very large [1]. From 2007 to 2016, foreign language professional undergraduate enrollment an average of about 200000 people a year [2], and most for non-English majors in colleges and universities are opened the English courses.…”
Section: Introductionmentioning
confidence: 99%